Exposure determinants of phthalates, parabens, bisphenol A and triclosan in Swedish mothers and their children - Kristin Larsson; Karin Ljung Björklund; Brita Palm; Maria Wennberg; Lennart Kaj; Christian H. Lindh; Bo A.G. Jönsson; Marika Berglund (Environment International, 2014)
Chemicals such as phthalates, parabens, bisphenol A (BPA) and triclosan (TCS), used in a wide variety of consumer products, are suspected endocrine disrupters although their level of toxicity is thought to be low. Combined exposure may occur through ingestion, inhalation and dermal exposure, and their toxic as well as combined effects are poorly understood.The objective of the study was to estimate the exposure to these chemicals in Swedish mothers and their children (6–11 years old) and investigate potential predictors of the exposure. Urine samples from 98 mother–child couples living in either a rural or an urban area were analyzed for the concentrations of four metabolites of di-(2-ethylhexyl) phthalate (DEHP), three metabolites of di-iso-nonyl phthalate (DiNP), mono-ethyl phthalate (MEP), mono-benzyl phthalate (MBzP) and mono-n-butyl phthalate (MnBP), methylparaben (MetP), ethylparaben (EthP), propylparaben (ProP), butylparaben, benzylparaben, BPA, and TCS. Information on sociodemographics, food consumption habits and use of personal care products, obtained via a questionnaire, was used to investigate the associations between the urinary levels of chemicals and potential exposure factors.There were fairly good correlations of biomarker levels between the mothers and their children. The children had generally higher levels of phthalates (geometric mean ΣDEHP 65.5 μg/L; ΣDiNP 37.8 μg/L; MBzP 19.9 μg/L; MnBP 76.9 μg/L) than the mothers (ΣDEHP 38.4 μg/L; ΣDiNP 33.8 μg/L; MBzP 12.8 μg/L; MnBP 63.0 μg/L). Conversely, the mother's levels of parabens (MetP 37.8 μg/L; ProP 13.9 μg/L) and MEP (43.4 μg/L) were higher than the children's levels of parabens (MetP 6.8 μg/L; ProP 2.1 μg/L) and MEP (28.8 μg/L). The urinary levels of low molecular weight phthalates were higher among mothers and children in the rural area (MBzP p = <0.001; MnBP p = 0.001–0.002), which is probably due to higher presence of PVC in floorings and wall coverings in this area, whereas the levels of parabens were higher among the children in the urban area (MetP p = 0.003; ProP p = 0.004) than in the rural area. The levels of high molecular weight phthalates were associated with consumption of certain foods (i.e. chocolate and ice cream) whereas the levels of parabens were associated with use of cosmetics and personal care products. Keywords: Biomonitoring, Children, Urine, Exposure sources, Biomarker, Consumer products